A gentle critique of the Greenhouse Development Rights framework. (14th June 2013) - Shockley, Kenneth E.
Abstract: The Greenhouse Development Rights (GDR) framework provides a promising attempt at fairly distributing the burdens of climate change. This brief review critically examines the framework, with a particular focus on the individualism that the authors take to provide much of the moral justification for their account. The review concludes that the particular role played by individualism in GDR both blinds the framework to certain crucial features of development and leads to difficulties in attributing historical emissions more properly tied to states and collective entities than to individuals. WIREs Clim Change 2013, 4:225–231. doi: 10.1002/wcc.215 This article is categorized under: Climate, Nature, and Ethics > Climate Change and Global Justice